Radiative mixed convective flow induced by hybrid nanofluid over a porous vertical cylinder in a porous media with irregular heat sink/source - Chu, Yuming; Khan, Umair; Ishak, Anuar; Zaib, Aurang; Sherif, El-Sayed M.; Waini, Iskandar; Pop, Ioan (Elsevier Ltd, 2021)
Purpose: Hybrid nanofluids have higher mechanical resistance, thermal conductivity, chemical stability, and physical strength when compared to normal nanofluids. Our approach in the current paper is to present a novel exploration comprising radiative mixed convection flow of hybrid nanofluids with irregular heat source/sink effect through a porous vertical cylinder immersed in a porous media. Both opposing and assisting flows are discussed. Methodology: The transmuted similarity ODEs are numerically worked out utilizing the assist of the bvp4c package in MATLAB for different values of physical parameters. The hybrid nanofluids contain a couple of nanoparticles namely aluminum and copper particles with water as base fluid. Findings: It was observed that fundamental similarity equations disclose double solutions (first and second branches) for buoyancy assisting and opposing flows. The drag force is enhanced due to the radiation as well as curvature parameters. In addition, the velocity declines due to heat source/sink and radiation parameter. Originality/value: The writers agree that all numerical outcomes are novel and have not previously been published for the current problem.